Synthesis reactions of neutron-rich isotopes of light elements - Penionzhkevich, Yu (Eurasian Journal of Physics and Functional Materials, 2026)
One of the most complicated problems of experimental nuclear physics is the synthesis of exotic nuclei near the boundaries of stability. These nuclei, as a rule, are 10 or more neutrons awayfrom stable nuclei, have a short lifetime (less than 1 ms) and low binding energy. All this determines special requirements to the choice of reactions for the synthesis of such nuclei and the method of their transportation and registration. Mainly, for the synthesis of exotic nuclei, reactions of fragmentation of the bombarding heavy ion, direct reactions of the types ( p,d) , (d, p) , (d,n) ,( d , 3 He), etc., as well as reactions of fission and deep inelastic transfer are used. Recommended Citation Penionzhkevich, Yu. E. (2021) "Synthesis reactions of neutron-rich isotopes of light elements," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 2, Article 1. DOI: https://doi.org/10.32523/ejpfm.2021050201